Apakah digitalisasi meningkatkan harapan hidup? Analisis panel data Provinsi Indonesia 2022-2024 - Putri, Yustika Mahayu; Hidayat, Budi (Journal of Economics Research and Policy Studies, 2025)
Digitalization has become a global and national priority to improve various aspects of life, including public services, infrastructure, education, economy, and healthcare. This study analyzes the impact of digitalization on life expectancy using panel data from 34 provinces in Indonesia for 2022–2024. Digitalization is measured using the Indonesia Digital Society Index (IMDI), while the dependent variable is life expectancy at birth. The econometric model was applied for the analysis with a fixed-effects panel data model, controlling for variables such as gross regional domestic product (GRDP) per capita, average salary, population density, average years of schooling, and unemployment rate. The results indicate that digitalization significantly impacts life expectancy, with a one-unit increase in the Indonesia Digital Society Index (IMDI) associated with a 1.6% increase in life expectancy. Additionally, years of schooling contribute positively, while the unemployment rate has an adverse effect. Improving digital literacy, education, and reducing unemployment are necessary to enhance society’s quality of life.